DESAIN DAN IMPLEMENTASI KENDALI MOTOR AC 3 FASA MENGGUNAKAN MODUL (VSD) VARIABLE SPEED DRIVE - Alimuddin Mappa; Alexander Jamlean; Isman Sarman (LPPM Poltek ST Paul, 2023)
Variable speed drive is used to convert AC voltage into DC voltage, then the DC voltage is converted again into AC voltage with the desired frequency with the aim of regulating the speed of the induction motor. The speed of the induction motor can be changed by changing the frequency value, so the variable speed drive is also called the variable frequency drive. The variable speed drive used is a Schneider Atv 12 variable speed drive with a power of 0.37 kw with a 3-phase induction motor load with a power of 0.18-0.37 kw. The test results prove that the rotation of the induction motor can be adjusted by changing the frequency.